REDISCOVERING TOURISTIC PHOTOGRAPHY IN BALI:: GREGOR KRAUSE AS A PIONEER - I Made Bayu Pramana (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
At the beginning of the Netherland-Indies colonial era in Bali, photography became an important medium that introduced Bali to the westerner. Photography in the realm of documentation in Bali began in 1912 by Gregor Krause, a German doctor who was commissioned by the Netherland-Indies colonial government to treat the cholera epidemy outbreak in southern Bali. Gregor Krause for the first-time photographed Bali from the viewpoint of community life, agriculture, religion, women and children, dance, markets, nature, culture and arts. Most of Krause's photographic works totalling more than 4000 frames were published in 1920, the photos in the book then played an important role as a media for promoting exotic Bali in the early tourism era, and inspired many Western photographers, artists, writers and explorers to come to Bali. The activities of the early travellers then published in the tourism promotion media in the form of books, posters, postcards, magazines, brochures and travel guides which published by the colonial government, shipping, airlines, and travel agents in various needs. This article discusses the role of Krause photography and analysis of Gregor Krause's photographic work as a photography pioneer at the beginning of the tourism era in Bali. Keywords: Colonial, Tourism, Photography, Bali, Gregor Krause, Pioneer